Genes encoding major light-harvesting polypeptides are clustered on the genome of the cyanobacterium Fremyella diplosiphon. - Conley, P B (1986)
The polypeptide composition of the phycobilisome, the major light-harvesting complex of prokaryotic cyanobacteria and certain eukaryotic algae, can be modulated by different light qualities in cyanobacteria exhibiting chromatic adaptation. We have identified genomic fragments encoding a cluster of phycobilisome polypeptides (phycobiliproteins) from the chromatically adapting cyanobacterium Fremyella diplosiphon using previously characterized DNA fragments of phycobiliprotein genes from the eukaryotic alga Cyanophora paradoxa and from F. diplosiphon. Characterization of two lambda-EMBL3 clones containing overlapping genomic fragments indicates that three sets of phycobiliprotein genes--the alpha- and beta-allophycocyanin genes plus two sets of alpha- and beta-phycocyanin genes--are clustered within 13 kilobases on the cyanobacterial genome and transcribed off the same strand. The gene order (alpha-allophycocyanin followed by beta-allophycocyanin and beta-phycocyanin followed by alpha-phycocyanin) appears to be a conserved arrangement found previously in a eukaryotic alga and another cyanobacterium. We have reported that one set of phycocyanin genes is transcribed as two abundant red light-induced mRNAs (1600 and 3800 bases). We now present data showing that the allophycocyanin genes and a second set of phycocyanin genes are transcribed into major mRNAs of 1400 and 1600 bases, respectively. These transcripts are present in RNA isolated from cultures grown in red and green light, although lower levels of the 1600-base phycocyanin transcript are present in cells grown in green light. Furthermore, a larger transcript of 1750 bases hybridizes to the allophycocyanin genes and may be a precursor to the 1400-base species.